Dry socket - clinical procedures review - Nieścior, Hubert; Bator, Damian; Wójcik, Magdalena; Szarpak, Julita; Dąbrowska, Justyna; Sereda, Dominika (Journal of Education, Health and Sport, 2020)
Introduction: Dry socket is a complication following extraction surgery. It usually appears between days 1 and 3 after extraction. The partially disorganized clot breaks down and healing is impaired. Material and methods: The latest reports available on the dry socket and its treatment using various methods were used. The NCBI database was used for this purpose, using the terms "dry socket" and "dry socket treatment". State of knowledge: Dry socket occurs as a complication in 1-5% of extraction sockets, while in the case of sockets after 3 mandibular molars, the percentage is as high as 38%. Risk factors may include: insufficient blood supply to the tissue, use of an excessive amount of anesthetic, hormonal contraception, smoking, traumatic surgery, failure to follow the doctor's instructions regarding the postoperative procedure. Chlorhexidine, warm saline, platelet plasma, hyaluronic acid-impregnated collagen sponges, resorbable collagen membranes and eugenol with lidocaine on Penghawar Djambi carrier can be used to treat dry socket. Summary: Dry socket is a medical condition. The unification of treatment recommendations is the goal of research on tools used in the context of a dry socket. Evaluation of profits and losses will allow to unify the recommendations and reduce the incidence of this complication.